2003
DOI: 10.1161/01.str.0000087171.34637.a9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of MK-801 in Different Rat Stroke Models for Permanent Middle Cerebral Artery Occlusion

Abstract: Background and Purpose-Permanent middle cerebral artery occlusion (MCAO) with the use of the suture technique causes hypothalamic damage with subsequent hyperthermia, which can confound neuroprotective drug studies. In the present study the neuroprotective effects of dizocilpine (MK-801) were compared in different permanent MCAO models with and without hypothalamic damage and hyperthermia. Methods-Sixty Sprague-Dawley rats were treated with MK-801 or placebo, beginning 15 minutes before MCAO, and assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…1,4,5,12 This complication was confirmed by MRI ( Figure 4) and postmortem examination in 1 out of 11 animals in group I (9%) and in 1 out of 14 rats in group II (7%). SAH can lead to serious side effects such as vasospasm and intracerebral hemorrhage, and thus can confound the results of experimental stroke studies.…”
Section: Subarachniod Hemorrhagementioning
confidence: 69%
See 2 more Smart Citations
“…1,4,5,12 This complication was confirmed by MRI ( Figure 4) and postmortem examination in 1 out of 11 animals in group I (9%) and in 1 out of 14 rats in group II (7%). SAH can lead to serious side effects such as vasospasm and intracerebral hemorrhage, and thus can confound the results of experimental stroke studies.…”
Section: Subarachniod Hemorrhagementioning
confidence: 69%
“…This causes hypothalamic infarction with associated pathologic hyperthermia that confounds neuroprotective drug evaluation. [3][4][5] The recently introduced macrosphere model has been developed to overcome this side effect by the intra-arterial embolization of 6 TiO 2 spheres that selectively block blood flow to the MCA main stem without obstructing the HA. This model avoids hypothalamic infarction and pathological hyperthermia but does not allow for reperfusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our results, Suzuki et al [6] reported that intravenous administration of MK-801 at the dose of 0.1 mg/kg immediately after middle cerebral artery occlusion showed neuroprotective effects without side effects. Moreover, Gerriets et al [5] also found that MK-801 was neuroprotective after macrosphere model of ischaemic brain injury in rats. Behavioural tests showed that MK-801 could improve both neurological deficits scores (motor function) and sedation assessment scores (level of arousal).…”
Section: Controlmentioning
confidence: 94%
“…Under pathological conditions, overactivation of these receptors cause an excessive amount of Ca 2+ influx into the nerve cells, which then triggers a variety of processes that can lead to necrosis or apoptosis [4]. In line with this, it has been shown that NMDA receptor antagonists reduce damage in animal models of stroke [5,6].…”
mentioning
confidence: 91%